Analysis of the use of fixed assets of enterprisesa - Trush, E. V.; Pererva, P. G. (Національний технічний університет "Харківський політехнічний інститут", 2023)
It is substantiated that recently the majority of enterprises in Ukraine, realizing the importance of the need to update fixed assets, are not able to carry out it efficiently and on time. This negatively affects the degree of wear of the enterprise equipment, the coefficient of its renewal, and the level of competitiveness of products.
Аналіз використання основних засобів підприємства
Keywords: fixed assets; analysis; efficiency; models; enterprises